Penguatan Kompetensi Kewirausahaan Remaja Melalui Kegiatan Edukatif di Teluk Pakedai - Hermawan, Veri; Mufrihah, Mazayatul; Putera, Muhammad Azril Adhika; Amirah, Laudza Bilqis; Ayu, Dwita Della; Fahrevy, Evky (CV. Ulil Albab Corp, 2026)
This community service activity aims to increase entrepreneurial interest among youth in Selat Remis Village, Teluk Pakedai District, Kubu Raya Regency. The main problem faced by the partners is the low interest of young people in starting a business, which affects the economic independence of the younger generation. The activities were carried out through entrepreneurship motivation seminars, creative product-making workshops, and direct mentoring for youth interested in entrepreneurship. The implementation methods included interactive material delivery, demonstrations, technical guidance, and direct practice mentoring until participants were able to produce and market products independently. The results of the activity indicated an increase in entrepreneurial interest, as reflected in several youths starting to engage in selling and successfully running small businesses independently. This activity is expected to be an initial step in fostering a creative, innovative, and economically independent young generation in Selat Remis Village.